The Morphophysiological Characteristics of Rice (Oryza sativa L.) Inoculated with Mycorrhizal Fungi at Different Salinity Levels: Karakter Morfofisiologi Tanaman Padi (Oryza sativa L.) dengan Inokulum Mikoriza pada berbagai Tingkat Salinitas - Rumzi Rumzi; Iwan Sasli; Tatang Abdurrahman (Agrifarm : Jurnal Ilmu Pertanian, 2026)
Soil salinity is one of the major limiting factors of soil fertility that directly affects rice growth and productivity. This study aimed to evaluate the role of mycorrhizal fungi in enhancing the growth and yield of rice plants under saline growing media conditions. The research was conducted at the Plant Seed Center, Peniraman Village, Sungai Pinyuh District, Mempawah Regency, from August to December 2025. The experiment was arranged in a split-plot design based on a randomized complete block design. The main plots consisted of without mycorrhizal fungi application and with mycorrhizal fungi application, while the subplots consisted of salinity levels of 0, 2, 3, 4, and 5 ppt. There were 10 treatment combinations, each replicated three times, with eight observation units, resulting in a total of 240 plants. The results showed that the application of mycorrhizal fungi increased rice productivity, as indicated by the grain weight per hill. Rice plants were able to tolerate soil salinity conditions up to 2 ppt, based on the variables of plant dry weight, panicle length, 1000-grain weight, and percentage of filled grains. No interaction was observed between mycorrhizal fungi application and salinity levels for all variables measured.